HfO2/HfS2 hybrid heterostructure fabricated via controllable chemical conversion of two-dimensional HfS2. Issue 39 (2nd October 2018) - Lai, Shen; Byeon, Seongjae; Jang, Sung Kyu; Lee, Juho; Lee, Byoung Hun; Park, Jin-Hong; Kim, Yong-Hoon; Lee, Sungjoo
Abstract : We demonstrate that HfO2, a high-K dielectric, can be prepared on the top surface of 2D HfS2 through plasma oxidation, which results in a heterostructure composed of a 2D van der Waals semiconductor and its insulating native oxide. Abstract : While preparing uniform dielectric layers on two-dimensional (2D) materials is a key device architecture requirement to achieve next-generation 2D devices, conventional deposition or transfer approaches have been so far limited by their high cost, fabrication complexity, and especially poor dielectric/2D material interface quality. Here, we demonstrate that HfO2, a high-K dielectric, can be prepared on the top surface of 2D HfS2 through plasma oxidation, which results in a heterostructure composed of a 2D van der Waals semiconductor and its insulating native oxide. A highly uniform dielectric layer with a controlled thickness can be prepared; the possibility of unlimited layer-by-layer oxidation further differentiates our work from previous attempts on other 2D semiconducting materials, which exhibit self-limited oxidation up to only a few layers. High resolution transmission electron microscopy was used to show that the converted HfO2 /HfS2 hybrid structure is of high quality with an atomically abrupt, impurity- and defect-free interface. Density functional theory calculations show that the unlimited layer-by-layer oxidation occurs because oxygen atoms can barrierlessly penetrate into the HfS2 surface and the extracted sulfur atoms are absorbed into the oxygen vacancy sites within HfO2 under O-rich conditions. A top-gated field-effect transistor fabricated with the converted HfO2 /HfS2 hybrid structure was found to exhibit a low interface trap density D it of 6 × 10 11 cm −2 eV −1 between the HfS2 channel and the converted HfO2 dielectric, and a high on/off current ratio above 10 7 . Our approach provides a low cost, simple, and ultraclean manufacturing technique for integrating 2D material into device applications.